Global inflation: The role of food, housing and energy prices - Miles Parker (European Central Bank (ECB), 2017)
This paper studies the role of global factors in causing common movements in consumer price inflation, with particular focus on the food, housing and energy sub-indices. It uses a comprehensive dataset of 223 countries and territories collected from national and international sources. Global factors explain a large share of the variance of national inflation rates for advanced countries - and more generally those with greater GDP per capita, financial development and central bank transparency - but not for middle and low income countries. Common factors explain a large share of the variance in food and energy prices.
Keywords: E31; E52; F42; 330; global ination; common factor; food prices; energy prices